(untitled) (Research, Society and Development, 2022)
A stroke is a medical emergency that happens when blood flow to the brain is interrupted. Without blood, your brain cells begin to die and this can cause severe symptoms, lasting disability, and even death. In this context, the present research aimed to make a comparison between the northeastern states regarding the incidence of ischemic and hemorrhagic stroke in the last 5 years. Research carried out in the DATASUS-Tabnet database, using the ICD-10 I64 categories for non-specific stroke and G45 for ischemic stroke, data referring to the northeast states in the period from 2016 to 2020 were collected, tabulated and analyzed in the Excel.Se observed a similar gender distribution in all states, with cases of death in person between 60 and over 80 years. For the CID-10 I64 stroke, the state of Bahia had the highest number of deaths, while for the G45 category, the state of Ceará had the highest number of deaths. As for the locations, non-specific strokes were more found in the state of Bahia, while ischemic strokes were mainly concentrated in the state of Ceará.